Interpreting the Past for the Public. - Soine, Jessica (My University, 2009)
This research was undertaken to provide a database of material from which to draw information to educate the regional residents about local archaeology and the history of the American Indian cultures in the Chippewa River Valley and Wisconsin. Each article is part of an electronic database of texts with accompanying photographs that can be utilized to create pamphlets, posters, or websites for educational purposes.
Color poster with text and images describing research conducted by Jessica Soine, advised by Robert J. Barth.
Keywords: Indians of North America--Wisconsin--Antiquities; Indians of North America--Wisconsin--Databases; Archaeology--Wisconsin--Chippewa River Valley; Archaeology--Wisconsin--Databases; Chippewa River Valley (Wis.)--Antiquities; Posters